Good human resource practices in Caribbean tourism (Commonwealth Secretariat LondonUS, 2005)
Provides helpful tips and resources on how to find, train, oversee, and keep good employees. Focuses on a selection of Caribbean companies.
Keywords: HUMAN RESOURCES